RANGE ATTACKS IN DISTRIBUTED COMPUTER NETWORKS AND INTERNET - Khoroshko, Volodymyr; Khokhlachova, Yuliia; Brailovskyi, Mykola; Kapustian, Mariia (Ukrainian Information Security Research Journal, 2023)
In this article, typical remote attacks and their implementation mechanisms are discussed in detail, as well as network traffic is analyzed, which allows to investigate the logic of work of a distributed computer network, i.e. to obtain an unambiguous correspondence of events that occur in the system and commands that are transmitted between objects system at the time of occurrence of these events. Based on network security research and information availability analysis, those possible remote information destructive effects (remote attacks) that can appear as unwanted effects at any time are described. Types of modification of information and information code are also considered in detail. It was determined that although the protection of information in distributed computer networks and the Internet is a broad and diverse topic, it is clear that Internet technologies are the driving force of development in this sector. Researching this problem is a very complex process and obtaining certain solutions is very important for information security. Modern attacks and, first of all, remote ones, are practically impossible to prevent, therefore, having information about the types and actions of remote attacks in distributed networks, it is possible to ensure the fight against them or at least reduce their impact on information in distributed computer networks and the Internet.